A value-based transcription of student choices into higher education branding practices. (2017) - Melanthiou, Yioula; Thrassou, Alkis; Vrontis, Demetris
Struggling in an incessantly changing and highly turbulent market environment, higher education institutions (HEIs) are increasingly turning to industry-style business practices to meet their strategic targets, grow or simply survive. Though still a subject of intense discussion, primarily on social and ethical grounds, the phenomenon is both undeniable and irreversible in the foreseeable future, for most countries. In this context, our research a) undertakes an extensive theoretical study into the subject; b) applies a qualitative, interview-based methodological approach to identify the underlying drivers of student choices regarding higher education; c) utilises contemporary marketing theories to transcribe the findings into HEI prescriptive branding and image-construction practices. The research ultimately develops a provisional value-based student choice branding image model towards practical implementation of the findings and directs future research towards validation, development and refinement.